Research and Innovation of Business Model of Shengu Town in Dinghu Mountain Under the Development of Forest-based Wellness Industry - Huang, Yanjun (Pacific International Journal, 2022)
China's Forest-based Wellness Care Industry started late, but in recent years, with people's increasingly strong pursuit of high-quality healthy life, driven by a series of policies, it has received more and more attention and involvement from social capital. How to innovate the business model of emerging industries deserves academic attention. This study takes Shengu Town in Dinghu Mountain as an example. Its business model under the background of industrial development has five characteristics: taking the middle and high consumption customer groups of all ages as the target customers, taking multi-industry integration as the value proposition, taking multi-path implementation as the value creation and delivery, taking tourism real estate as the value capture, and taking rural revitalization as the social responsibility. Based on these characteristics, according to the customer segmentation theory and the business model innovation model, this study puts forward innovative suggestions for timesharing model and alliance model.